Effects of helium irradiation damage on deuterium plasma-driven permeation through tungsten coated RAFM steel - Yue Xu; Xiao-Ping Tian; Hong-Yan Tan; Hai-Ying Fu; Jun-Jie Ni; Lai-Ma Luo; Yu-Cheng Wu (Nuclear Fusion)
In future fusion reactors, the first wall will be irradiated with hydrogen fuel (deuterium (D), tritium (T)) and helium (He) with low energies. In this work, the effects of He plasma irradiation on D permeation through tungsten (W) coated reduced activation ferritic/martensitic (RAFM) steel were systematically investigated by performing plasma-driven permeation (PDP) measurements in the temperature range of 523–833 K. The W coatings were prepared by magnetron sputtering. He plasma irradiation with different fluences was carried out in a linear plasma device. The results showed that as He irradiation fluence increased, the surface damage of W coatings intensified, resulting in a high steady-state D-PDP flux and effective diffusion coefficient. The effect of incident ion energy on D-PDP was also influenced by He pre-irradiation. After He irradiation with a fluence of 6.0 × 10 ^24 He m ^−2 , the D-PDP flux was found to decrease with increasing incident ion energy despite the fact that the sample temperature was gradually increasing. The He pre-damage affected the overall D transport by re-balancing the bulk diffusion and surface recombination processes, therefore determining the PDP flux. D-PDP through W + RAFM under simultaneous D + He mixture plasma exposure was studied as well. The results indicated that the presence of He reduced the ionization rate of the D plasma and decreased D-PDP flux. D-PDP regime under the mixture plasma exposure was verified by calculating the transport parameter. It was found that the D-PDP regime was not changed by He introduction, which remained in the RD regime (recombination-limited D release from upstream surface and diffusion-limited D release from downstream surface).